Model Konseptual Perancangan Fasilitas Industri Konveksi Pakaian dengan Soft System Methodology - Alfathsyah, Arrasyid; Nurhasanah, Nunung; Zakaria, Siti Wardah; Tripiawan, Wawan (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
Facility design refers to the method of organizing factory facilities to support the efficiency of the production process and the effectiveness of production results. This improvement is done by updating the design of previous facilities or designing a complete facility that has not yet been built. In designing this facility design system, Soft System Methodology (SSM) was used. SSM is a structured approach to information system development that is used to understand the problem thoroughly, design conceptual models, assess the feasibility and desired changes, and then implement them into reality. In this research, SSM proved to be a highly effective framework for designing facility design systems in the context of the clothing convection industry. SSM includes abstract problem mapping, needs analysis of stakeholders involved in the system, CATWOE analysis, depiction of desired and undesired inputs and outputs through IO Diagram, expression description through Rich Picture, and grouping of core activities with Conceptual Modeling. The result of this research is a description that is traceable to the problem situation that exists in the facility design system so that it can know and master the involvement of actors in the system and the relationship between actors and activities that take place.Keywords – Clothing Convection Industry, Facility Design, Soft System Methodology(SSM), System Approach.